ANALISA INDEKS HARGA KONSUMEN TERHADAP UPAH KARYAWAN PADA CV. SIMETRIZ DESIGN CONSULTANT KUTACANE - maufira, Rila (MANABIS: Jurnal Manajemen dan Bisnis, 2022)
CV. Simetriz Design Consultant Kutacane, is a trading company engaged in Architectural Design, which has a vision and mission of integrated and comprehensive services in the planning and supervision of Civil architecture and environmental planning. In using employees, the company must pay attention to, utilization, development, assessment, provision of remuneration, ways to design planning systems, employee preparation, career management, performance evaluation, employee compensation, and labor relations. In this research, the background of the problem is that the Compensation Function is the provision of direct and indirect remuneration in the form of money or goods to employees as compensation for the services (output) that employees provide. The identification of the problem in this research is whether the salary/wages received by the employee have been able to meet the needs. So in this study formulate several problems, that the salary received is not enough to meet the needs seen from the ability of wages seen from purchasing power. This research is descriptive qualitative, data collection method with field research using direct observation and interview methods on the research object to obtain an overview of the research subject. From the results of the study, obtained data, the number of employees on the CV. Simetriz Design Consultant Kutacane numbered 13 people, consisting of 11 men and 2 women 1.88% 1.65%, 1.416%, 0.944 % , Female people, the remuneration provided is in the form of salary, the President Director is given a salary of Rp. 4,000 .000,-/Month, meaning that based on the specified UMP the wages earned are able to meet the consumer price index of 1.88%, the Deputy Director is given a remuneration of Rp. 3,500,000,-, 1.65%, while the Experts are given a salary IDR 3,000,000,- and subordinates are given IDR 2,500,000 and IDR 2,000,000/month, respectively. 0.944 %